The Impact of Implementation Strategic Management and Technology on SMEs in South Sulawesi - Hendriadi; Megawaty; Muh. Zabir Zainuddin; Badaruddin (International Journal of Management and Education in Human Development, 2022)
The increasingly dynamic market conditions and competition between companies encourage business owners, including small and medium business owners (SMEs) in Indonesia and other countries to understand how SMEs can maintain or improve marketing and financial performance in the era of digitalization. To compete, strategic management and expert policies encourage companies, including SMEs to apply practices in the field of strategic management in today's digitalization era. This study aims to measure how strong the influence of implementing strategic management practices and digitalization on the performance of SMEs in Sulawesi-South Indonesia (Makassar, Gowa, Maros, & Pare-Pare), especially performance related to sales turnover, break-even point (BEP), and profit. This study uses quantitative methods with primary data and data sources through the interview process and questionnaires. The interview process was conducted with the heads of small and medium enterprises (SMEs) in South Sulawesi (Makassar, Gowa, Maros, & Pare-Pare), while the questionnaires were distributed directly to 200 respondents by survey officers. Of the 200 questionnaires distributed to respondents, 180 of them (90%) met the requirements for processing and analysis. The results showed that Strategic Planning had a negative and significant effect on the sales volume of SMEs, Strategic Planning had a positive and insignificant effect on the BEP of SMEs, Strategic Planning had a negative and significant effect on SME Business Profit, Implementation Strategy had a negative and insignificant effect on the volume SME sales, Implementation Strategy has a positive and insignificant effect on SME BEP, Implementation Strategy has a negative and insignificant impact on SME Business Profits, Strategic Evaluation has a positive and significant impact on SME sales volume, Strategic Evaluation has a positive and significant impact on SME BEP, Strategic Evaluation has a negative and insignificant effect on SME operating profit, the use of technology has a positive and insignificant effect on the sales volume of SMEs, the use of technology has a negative and negative effect. not significant to the BEP of SMEs, the use of technology has a positive and significant effect on the operating profit of SMEs.